2021
DOI: 10.1098/rstb.2020.0390
|View full text |Cite
|
Sign up to set email alerts
|

The bouba/kiki effect is robust across cultures and writing systems

Abstract: The bouba/kiki effect—the association of the nonce word bouba with a round shape and kiki with a spiky shape—is a type of correspondence between speech sounds and visual properties with potentially deep implications for the evolution of spoken language. However, there is debate over the robustness of the effect across cultures and the influence of orthography. We report an online experiment that tested the bouba/kiki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 101 publications
(183 reference statements)
1
50
0
1
Order By: Relevance
“…Our replication attempts successfully replicated two findings (Klink, 2000;Shrum et al, 2012) and partially replicated one of them (Yorkston and Menon, 2004). This is consistent with the argument that sound symbolism is robust and found in diverse cultures (Cwiek et al, 2022). Among sensory marketing research, the reliability of the findings might differ depending on the type of sensory stimuli.…”
Section: Which Findings Can or Cannot Be Replicated?supporting
confidence: 86%
“…Our replication attempts successfully replicated two findings (Klink, 2000;Shrum et al, 2012) and partially replicated one of them (Yorkston and Menon, 2004). This is consistent with the argument that sound symbolism is robust and found in diverse cultures (Cwiek et al, 2022). Among sensory marketing research, the reliability of the findings might differ depending on the type of sensory stimuli.…”
Section: Which Findings Can or Cannot Be Replicated?supporting
confidence: 86%
“…This latter experiment on shape phonosymbolism had a wide impact on experimental psychology and linguistics: Several studies managed to replicate Köhler's results, corroborating the psychological reality of the so‐called “maluma–takete” effect (Köhler, 1947 ; Werner, 1948 , 2011 ) or “bouba‐kiki” effect, referring to the pseudowords employed by Ramachandran & Hubbard ( 2001 ). These research efforts set the stage for a number of experiments that repeatedly reported the same phonovisual correspondences at different developmental stages (Maurer, Pathman, & Mondloch, 2006 ; Ozturk, Krehm, & Vouloumanos, 2013 ; Pejovic & Molnar, 2017 ) and in various linguistic, geographical, and cultural contexts (Bremner et al., 2013 ; Ramachandran and Hubbard, 2001 ; Chen, Huang, Woods, & Spence, 2016 ; Shinohara & Kawahara, 2010 ; Ćwiek et al., 2021 ). The results of the studies on shape and magnitude symbolism were complemented by other findings that related to different properties of the visual modality, such as color (Johanssohn, Anikin, & Aseyev, 2020 ) and lightness (Hirata, Ukita, & Kita, 2011 ), to their respective phonetic signs.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the sound of round is spectrally low and temporally smooth . Surprisingly, while these simple acoustic properties have recently been mentioned for possibly being at the origin of the bouba-kiki effect 12 , they have never been tested.…”
Section: Resultsmentioning
confidence: 99%
“…The second issue deals with the underlying mechanisms that could explain such audiovisual associations and whether the bouba-kiki effect is innate or can be learned through exposure to audiovisual regularities in the environment. In spite of being very robust in adults and shared by most language and cultures 11 , 12 , a meta-analysis 18 showed that infants in their first year were only sensitive to a bouba effect (i.e. a tendency to associate bouba sounds with round shapes).…”
Section: Introductionmentioning
confidence: 99%